2017
DOI: 10.1134/s000629791709005x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light intensity under different photoperiods on expression level of carbonic anhydrase genes of the α- and β-families in Arabidopsis thaliana leaves

Abstract: Changes in expression levels of genes encoding carbonic anhydrases α-CA1, α-CA2, α-CA4, β-CA1, β-CA2, β-CA3, β-CA4, β-CA5, and β-CA6 in Arabidopsis thaliana leaves after light increase from 80 to 400 µmol PAR quanta·m·s were investigated under short day (8 h) and long day (16 h) photoperiods. The expression of two forms of the gene, At3g01500.2 and At3g01500.3, encoding the most abundant carbonic anhydrase of leaves, β-CA1, situated in chloroplast stroma, was found. The content of At3g01500.3 transcripts was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 27 publications
5
27
0
Order By: Relevance
“…The effective quantum yield of photosynthetic electron transport at saturating light intensity and CO 2 concentration was higher in mutants than in the WT, while nonphotochemical chlorophyll fluorescence quenching (NPQ ) was lower [13,37,134,135]. The content of transcripts of the At4g20990 gene encoding α-CA4 was two times higher under high (400 μmol quanta m −2 s −1 ) than under low illumination (80 μmol quanta m −2 s −1 ) when grown under "short-day" (8 hours day/16 hours night) and 16 times higher under "long-day" conditions (16 hours day/8 hours night) [6]. Thus, the above-described effects of the At4g20990 gene knockout are consistent with a significant increase in the expression level of this gene in plants under high illumination; these are the conditions where the activation of NPQ , which protects PSII from photoinhibition, is important.…”
Section: Ca In Granal Thylakoid Membranesmentioning
confidence: 96%
See 3 more Smart Citations
“…The effective quantum yield of photosynthetic electron transport at saturating light intensity and CO 2 concentration was higher in mutants than in the WT, while nonphotochemical chlorophyll fluorescence quenching (NPQ ) was lower [13,37,134,135]. The content of transcripts of the At4g20990 gene encoding α-CA4 was two times higher under high (400 μmol quanta m −2 s −1 ) than under low illumination (80 μmol quanta m −2 s −1 ) when grown under "short-day" (8 hours day/16 hours night) and 16 times higher under "long-day" conditions (16 hours day/8 hours night) [6]. Thus, the above-described effects of the At4g20990 gene knockout are consistent with a significant increase in the expression level of this gene in plants under high illumination; these are the conditions where the activation of NPQ , which protects PSII from photoinhibition, is important.…”
Section: Ca In Granal Thylakoid Membranesmentioning
confidence: 96%
“…The data on the decrease in photosynthetic activity, as well as the ability to accumulate starch in plants with a knockout of the gene encoding α-CA1 [116], may indicate the role of α-CA1 in photosynthesis and the possibility that this CA is involved in CO 2 supply to Rubisco. Using primers designed for possible alternative splicing of the template RNA of the At3g01500 gene encoding β-CA1, two isoforms were found to be present in the leaves of Arabidopsis [6]. An increase in plant illumination led to a change in the content of transcripts of most genes encoding CA of chloroplasts, and a significant difference was observed in the expression intensity of α-CA1 genes and two forms of β-CA1.…”
Section: Carbonic Anhydrases In Chloroplasts Of C3 Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene expression of all β family CAs has been demonstrated in Arabidopsis thaliana leaves [10,12], as well as the expression of three α family genes encoding α-CA1, α-CA2 and α-CA3 [10]. Rudenko et al [13] did not detect expression of the latter, but demonstrated that arabidopsis leaves contain At4g20990 gene transcripts encoding α-CA4 found among thylakoid membrane proteins [14]. In arabidopsis, there are 6 active β-ca genes, and excepting β-ca3 the others have from 2 to 5 forms, resulting from alternative splicing predominantly in untranslated regions of one or two exons by the 3’ ends, and more often, by the 5’ ends of the corresponding RNAs.…”
Section: Ca Gene Expression In Arabidopsis Leavesmentioning
confidence: 99%